The Role of Chinese Tourists in Enhancing Pokhara’s Economy and Quality of Life - Sharma, Laxmi Kanta; Paudel, Vishal (THE ACADEMIA, 2025)
This study explores the impact of Chinese tourists on Pokhara’s local economy and the Quality of Life (QoL) . Through a survey of 400 Chinese visitors, the study assesses their satisfaction levels across various domains (e.g., leisure, cultural experiences, accommodation) and explores the economic contributions of their tourism spending. Findings indicate significant contributions to the local economy, particularly in terms of revenue generation and job creation, alongside a strong positive correlation between tourist satisfaction and perceived QoL. Further through in-depth interviews of 50 tourism operators, this paper also highlights the social and cultural effects of increasing Chinese tourism, with recommendations for promoting sustainable tourism practices to maximize benefits for both tourists and the local community. The findings suggest that Chinese tourism has the potential to contribute significantly to Pokhara’s economic and social development, but this growth must be managed responsibly to avoid over-tourism and preserve local culture.